PENGARUH KUALITAS PELAYANAN, PROMOSI, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DALAM MENGINAP DI HOTEL LE MERIDIEN JAKARTA - Mochamad Erland Prawiratama; Darwin Raja Unggul Saragih (LPPM Universitas Asa Indonesia, 2023)
The purpose of this study is to analyze and determine the impact of service quality, promotion and brand image on the decision to stay at Hotel Le Meridien Jakarta. The method used by researchers is descriptive quantitative method and the population of this study are all guests staying at Hotel Le Meridien. The sampling technique used is non-probability method with accidental sampling technique with a total sample of 80 respondents. Researchers used 20 respondents to test the validity and reliability. Data analysis used in this research is multiple linear regression analysis through SPSS ver. 24. The results of the analysis show that service quality partially has no significant effect on overnight purchase decisions, promotion has a significant effect on overnight purchase decisions, brand image partially has a significant effect on overnight purchase decisions. Service quality, promotion, and brand image have a significant and positive simultaneous effect on the decision to stay.